Schaalia turicensis endometritis in a diabetic patient: MALDI-TOF MS overcomes diagnostic barriers in a non–IUD-associated case - Liu, Yan; Li, Mei; Ding, Yunyun; Gao, Yong; Li, Tuantuan; Wang, Xiaowu (Frontiers in Medicine, 2025)
Schaalia (Formerly Actinomyces) turicensis is a single-cell prokaryotic microorganism and a common component of the normal human oral flora. If it enters other parts and causes infection, it may lead to actinomycosis. We present the case of a 74-year-old female patient from Fuyang who developed bacterial endometritis due to Schaalia turicensis. The bacterial culture of painless cervical dilation with drainage and curettage showed slow-growing, Gram-positive rods, which were identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) as Schaalia turicensis. The patient was initially treated empirically with cefathiamidine and tinidazole for 3 days, with no improvement of symptoms. Subsequently, the treatment regimen was adjusted to intravenous infusion of amoxicillin and clavulanate potassium (1.2 g) every 8 h for 7 days. Resulted in significant alleviation of the patient’s symptoms. Clinicians should be aware of other types of infections that may be caused by Schaalia turicensis.